Goal Commitments and the content of thoughts and dreams: basic principles - Klinger, Eric (Frontiers in Psychology, 2013)
A few empirically supported principles can account for much of the thematic content of waking thought, including rumination, and dreams. (1) An individual’s commitments to particular goals sensitize the individual to respond to cues associated with those goals. The cues may be external or internal in the person’s own mental activity. The responses may take the form of noticing the cues, storing them in memory, having thoughts or dream segments related to them, and/or taking action. Noticing may be conscious or not. Goals may be any desired endpoint of a behavioral sequence, including finding out more about something, i.e., exploring possible goals, such as job possibilities or personal relationships. (2) Such responses are accompanied and perhaps preceded by protoemotional activity or full emotional arousal, the amplitude of which determines the likelihood of response and is related to the value placed on the goal. (3) When the individual is in a situation conducive to making progress toward attaining the goal, the response to goal cues takes the form of actions or operant mental acts that advance the goal pursuit. (4) When circumstances are unfavorable for goal-directed operant behavior, the response remains purely mental, as in mind-wandering and dreaming, but still reflects the content of the goal pursuit or associated content. (5) Respondent responses such as mind-wandering are more likely when the individual is mentally unoccupied with ongoing tasks and less likely the more that is at stake in the ongoing task. The probability of respondent thought is highest during relaxed periods, when the brain’s default-mode network dominates, or during sleep. The article briefly summarizes neurocognitive findings that relate to mind-wandering and evidence regarding adverse effects of mind-wandering on task performance as well as evidence suggesting adaptive functions in regard to creative problem-solving, planning, resisting delay discounting, and memory consolidation.